Oral contrast improves soft tissue matching in image guided radiation therapy for gastrointestinal (GI) tumors - Chu, K; Eccles, C; Baker, T; Durrant, L; Holyoake, D; Robinson, M; Mukherjee, S; Hawkins, M (Elsevier, 2016)
The lack of soft tissue contrast and artifacts due to variable gas filling make image guidance in precision radiation therapy for GI tract challenging. Anatomical structures in the tumor proximity can be used as surrogates as bony landmarks may be some distance from the target and inappropriate for target localization. We propose that oral contrast may aid in reproducible soft tissue visualization at treatment delivery and it is less invasive than fiducial marker insertion. This may be more useful in patients undergoing radiation therapy for hepatobiliary tract tumors where duodenal identification will aid in safe treatment delivery.